Recenzja książki: Städtebau im Nationalsozialismus. Angriff, Triumph, Terror im europäischen Kontext 1933–1945 - Grzeszczuk-Brendel, Hanna (Artium Quaestiones, 2025)
Städtebau im Nationalsozialismus. Angriff, Triumph, Terror im europäischen Kontext 1933–1945 presents a comprehensive overview of the achievements of the Third Reich, primarily within Germany. In addition to the main themes, the authors address topics that are rarely discussed in general studies, such as camp layouts. They also describe the mechanisms of power in spatial design, from administrative organization to the propagandistic tasks assigned to architecture and urban planning. The book proposes a methodological expansion of the concept of Städtebau. In this review, written from the perspective of a Polish scholar, attention is drawn to issues that are often omitted or discussed in only a cursory manner, such as Nazi activities in occupied territories, for which numerous projects were developed and treated as models for the future.